Karaí Arandú in the Mercosul Biennial: guarani education as a possibility for a decolonial aesthetics - Bergamaschi, Maria Aparecida; Melo (Universidade Federal do Rio Grande do Sul – UFRGS, Porto Alegre/RS, Brazil), Dannilo Cesar Silva (Revista Brasileira de Estudos da Presença, 2022)
This article discusses education, aesthetics and possibilities for a decolonial aesthetics, based on an experience we call (inter)cultural mediation in a Guarani school and an art exhibition at the 10th Mercosul Biennial. The concept of school (located in the indigenous territory) as a border space contributed to the understanding of a border thinking, which escapes the modern western canon. The (inter)cultural mediation proved to be useful as a method for je guata – a walking –, an investigative walking, performed with a school group of Guarani people.